Improving The Competence of Graduates of Theology Study Programs Based on Futuristic Curriculum in The Era Smart Society 5.0 - Saragih, Erman Sepniagus; Tamba, Tiffany; Hutabarat, Eduward Hottua; Situmorang, Kasih; Situmorang, Ribka (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
There has been a decline in the absorption of Bachelor of Theology graduates in the last 5 years, and more than 55% of graduates do not work according to their profile. The purpose of this study is to analyze efforts to improve graduate competency based on futurism as a solution to increasing the absorption of graduates of the Theology study program. The research method uses qualitative descriptive with a focus group discussion approach, surveys, and document analysis. The subjects in this study were internal stakeholders and external stakeholders of the study program. The data analysis used was triangulation. Data were collected based on categories and coding based on discussion results in the form of perceptions, opinions, criticisms, and suggestions; identifying themes and patterns; reinterpreting findings, synthesis, and conclusions. The results are as follows: First, the study program designs a futuristic curriculum that is relevant, effective, and adaptive. Second, professional guarantees are a paradigm in designing study materials for the learning process and learning evaluation. Third, important soft skills are innovative, collaborative, adaptive, and integrative. The conclusion is that the futuristic curriculum is an accumulation of commitment to the quality of learning management, starting from input, process, evaluation, control, and improving graduate competency.